A COUPLED MODEL FOR TSUNAMI RUN UP SIMULATION - Iryanto
Modeling wave run up in coastal zones using particle method requires a high computational cost. To reduce the cost, a coupled model of Navier Stokes equations (NSE) and Shallow Water Equation (SWE) has been proposed; the SWE is solved using a staggered scheme, whereas NSE is integrated using the Smoothed Particle Hydrodynamics (SPH). This coupled model has been studied thoroughly in [13]. In this research, this coupled model is used for simulating solitary wave run up on a sloping beach. Herein the simulation is also did using the pure SWE and the pure NSE. Our simulations are in good agreement compared with the run up height of Synolakis obtained experimentally in [4, 5]. Simulations of wave overtopping of a seawall using the coupled-model are also performed.